Queen of Ants In the Qur'an Surah An-Naml verse 18 - Akrom, Muhammad Fatih Kanzul; Rhain, Ainur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The discussion of ants in the Qur'an is found in surah an-Naml verse 18. This critical study of ants is found in the context of language discussion and laboratory research. The beginning of the spirit of rise in this discussion was a critical study of the translation of the meaning of Namlatun which translates to "an ant". Though lafadz namlatun should mean a female ant. The purpose of this research is to explore the meaning of language and match it with field research conducted in biological laboratories. Research on this discussion begins by departing from the study of texts that refer to the words Qaalat, Namlatun, an-Naml, and Udkhuluu. The results of the discussion of this article are expected to contribute knowledge that explains the world of ants as a balancer of forest ecosystems and the earth in general, because the presence of ants is a benchmark for the health of a food chain system in a forest.